Factores determinantes para mejorar la calidad del sector salud en el Perú (2010-2016) - García Calderón Díaz, Otto Miguel (2021)
Health is a right to physical, mental and social well-being that every human should be able to access and provide that coverage, granted by the State, is one of the objectives of Peru. Likewise, health and the economy are closely related both from the perspective of population well-being as a fundamental factor for productivity and human capital formation and in the influence that a good health system has on the development of the economy in a country. Therefore, making the right decisions about the correct investment of the public budget in this sector is essential to improve the economy along with the quality of health within any country. In this work, the quality of health is measured through the percentage of registered sick population and the degree to which it is affected is analyzed against five independent variables: Number of Doctors per 10,000 Inhabitants, Number of Nurses per 10,000 inhabitants, Annual Public Budget Awarded to the Health Sector, Health Infrastructure per Km2 and Years of Education in People Over 15 Years of Age. What's more; The study works with the information of the National Institute of Statistics and Informatics (INEI) under a data panel analysis of random effect on the data base used. The results show that investment in infrastructure is not very effective in improving health quality, unlike investing in prioritizing having a greater number of doctors per inhabitant; contrary to prioritizing the increase in nursing professionals, regardless of the variation of any other factor. The conclusions demonstrate the importance of the study to understand and provide recommendations that allow the development of effective policies that improve the quality of health in the country.